2021
DOI: 10.1049/nbt2.12054
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential and in vitro cytotoxicity study of polyvinyl pyrollidone‐stabilised silver nanoparticles synthesised from Lysinibacillus boronitolerans

Abstract: The main emphasis herein is on the eco‐friendly synthesis and assessment of the antimicrobial potential of silver nanoparticles (AgNPs) and a cytotoxicity study. Silver nanoparticles were synthesised by an extracellular method using bacterial supernatant. Biosynthesised silver nanoparticles were characterised by UV‐vis spectroscopy, transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, dynamic light scattering, and zeta potential analysis. The synthesised silver nanoparticles exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 74 publications
(81 reference statements)
5
3
1
Order By: Relevance
“…It has been shown that silver nanoparticles synthesized using an aqueous extract of Eucalyptus camaldulensis leaves and PVP as a stabilizing agent had no antibacterial properties because there was no zone of inhibition on the agar plates. This result conflicts with previous works that study the antibacterial properties of silver nanoparticles capped with PVP [ 36 , 50 ]. The absence of antibacterial activity is related to the formation of PVP layer around silver nanoparticles, which prevented the release of silver ions.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…It has been shown that silver nanoparticles synthesized using an aqueous extract of Eucalyptus camaldulensis leaves and PVP as a stabilizing agent had no antibacterial properties because there was no zone of inhibition on the agar plates. This result conflicts with previous works that study the antibacterial properties of silver nanoparticles capped with PVP [ 36 , 50 ]. The absence of antibacterial activity is related to the formation of PVP layer around silver nanoparticles, which prevented the release of silver ions.…”
Section: Resultscontrasting
confidence: 99%
“…This study highlights the absence of any antibacterial activity for silver nanoparticles prepared using PVP. To the best of our knowledge, there is no similar results have been reported earlier in the literatures [ 36 , 37 ]. This result support the benefit of coated silver nanoparticles with PVP to control the release ratio of silver ions and reduce the toxicity effect of AgNPs against living cells especially for medical and pharmacology applications as drug delivery systems and wound healing without any side effects [ 38 ].…”
Section: Introductionsupporting
confidence: 53%
“…When in presence of a CS-HAp scaffold, active Fn showed similar red-shifting performance ( Figure 4 a) with shifts as long as 80 nm between the 8 h and 32 h time points ( Table 2 ).The morphology of C2C12 cells was observed to be normal with a high percentage of confluence, which indicated that the NPs had no observable negative impact on the cell culture regardless of the treatment up to 32 h ( Figure 4 b). This result is in keeping with findings in the literature, which reports that C2C12 cells exposed to low concentrations of silver nanoparticles show no negative effect on morphology or cytotoxicity between 0.25 and 2 ug/mL [ 29 ].…”
Section: Resultssupporting
confidence: 92%
“… 85 The biogenically synthesized AgNPs from L. boronitolerans has shown significant cytotoxic action against C2C12 muscle cell line that leads to distortion of cellular membrane in a concentration dependent manner. 86 Therefore, the result validates that green synthesized nanoparticles CgAgNPs can serve as a potential cytotoxic as well as anti-proliferative agent against the breast cancer cells.…”
Section: Resultssupporting
confidence: 64%